Subsidiarna zaščita v evropskem in mednarodnem azilnem sistemu - Zagorc, Saša (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2018)
EU asylum law has without doubt a significant impact on international asylum law. The article focuses on the question if and how the subsidiary protection, the invention of the EU asylum law, should be extended to the international legal level. The EU has already been criticized for trying to replace the international refugee protection regime with the Qualification Directive rather than complementing it. Noting that the subsidiary protection is a subject of controversy within the EU itself regarding its interpretation and differences in use among the Member States, the criticism carries even more weight. The first part of the article presents the development and codification of complementary protection in the EU. The second part deals with the issue of discrimination among persons with refugee status and subsidiary protection. In the third part, current impact of the institute on the international asylum system is examined, while the last section gives a stance on the rationality and suitability of the application of subsidiary protection to the international level.
Keywords: asylum; azil; international protection; kvalifikacijska uredba; mednarodna zaščita; Qualification Regulation; subsidiarna zaščita; subsidiary protection